The Role of Educational Content in a Digital Marketing Strategy - Knihová, Ladislava (Communication Today, 2021)
Being under the pressure of uncertain times, galloping technology and dynamic changes in customer behaviour, companies hold their business managers accountable for fostering greater organisational achievements. While marketing budgets are shrinking, marketing professionals must deal with ongoing media fragmentation and declining advertisement performance. In their attempt to seek innovative communication channels, companies have started to recognise the high potential of customer education. This study’s objective is to identify, analyse and interpret the role of educational content in a digital marketing strategy. Educational content, formats and platforms are examined with the aim of suggesting efficient changes in the design of digital communication strategies appropriate to technology brands. The author has devised a Digital Communication Maturity Assessment Model as a tool for companies to carry out a reliable internal audit of digital communication processes. Based on the Fogg Behaviour Model, new types of customer relationships can be built with the help of relevant educational content which has been carefully crafted and adapted for customer-immersive learning. The insight into educational content implementation in technology brands’ digital communication represents an added value to this study. To further elaborate on the topic, the author suggests new opportunities for future research as well as specific research avenues.